Plano Municipal de Educação de Rio Claro - SP: desafios e perspectivas na garantia do direito à educação - Silva, Mariana Aparecida da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This work aims to monitor the formulation and conduct of the first Municipal Education Plan (SMEs) in the city of Rio Claro / SP, as an educational policy instrument, trying to identify how society mobilized for the construction of the plan, its proposals, the possible tensions between different social groups active in it and how they are defined by the Government in the final text the actions and goals concerning early childhood education and primary education, to ensure, in the time limit established by the Plan, the achievement the rights already enshrined in the legal framework. The issues that underlie this work moved the interest in verifying the construction process of the SMEs in order to unravel how the document will include proposals and strategies in order to ensure the right to education, understanding this right in its broadest sense, bound to ensure not only access to formal education, but to stay in it and academic success. Our intent was to determine which way the Municipal Plan of Education of Rio Claro / SP was being built (as per ?, who ?, what for?), And it ensures or not the conditions for public school meets, in fact, their nature and exercise their specificity to effect, even within the limits of bourgeois democracy, the rights proclaimed in the normative legal instruments. In this sense, we analyze the goals and two versions of the SME strategies: a) the wording drawn from the synthesis of seminars on 15 and 16 July 2012 (1st version) and, b) the wording after the review by COMERC (2nd version), respectively, related to the topics: kindergarten 4-5 years early childhood education 0-3 years basic education, access, literacy, extension of the school day, education quality, permanence, democratic management, expansion school funding and journey. We also performed the comparison of the proposals of the SME approved PNE light. The research anchored in documents and literature analysis, and in the involvement of...

Este trabalho tem o objetivo de acompanhar o processo de formulação e tramitação do primeiro Plano Municipal de Educação (PME) do município de Rio Claro/SP, como instrumento de política educacional, tentando identificar como a sociedade mobilizou-se para a construção do referido plano, suas propostas, as possíveis tensões entre os diversos grupos sociais nele atuantes e como serão definidos pelo Poder Público no texto final as ações e metas concernentes à educação infantil e ao ensino fundamental, para garantir, no limite do tempo estabelecido pelo Plano, a concretização dos direitos já consagrados em âmbito legal. As questões que moveram este trabalho perpassam o interesse em verificar o processo de construção do PME de modo a desvendar de que forma o documento contemplará propostas e estratégias, a fim de garantir o direito à educação, entendendo esse direito em seu sentido mais amplo, vinculado à garantia não apenas de acesso à educação formal, mas à permanência nele e ao sucesso escolar. Nosso intento foi verificar de qual maneira o Plano Municipal de Educação de Rio Claro/SP foi sendo construído (como?, por quem?, para quê?), e se ele assegura ou não as condições para que a escola pública cumpra, de fato, sua natureza e exerça sua especificidade, para efetivar, mesmo nos limites de uma democracia burguesa, os direitos proclamados nos instrumentos jurídicos normativos. Neste sentido, analisamos as metas e estratégias de duas versões do PME: a) a redação elaborada a partir da síntese dos seminários dos dias 15 e 16 de julho de 2012 (1ª versão) e, b) a redação dada após a revisão feita pelo COMERC (2ª versão), respectivamente, referentes aos temas: educação infantil de 4 a 5 anos, educação infantil de 0 a 3 anos, ensino fundamental, acesso, alfabetização, ampliação da jornada escolar, qualidade da educação, permanência, gestão democrática, ampliação da jornada escolar...
Keywords: Plano Nacional de Educação (Brasil); Education; Educação; Políticas públicas; Educação e Estado; Direito à educação; Educação de crianças; Ensino fundamental; Rio Claro (SP)